Effect of feeding protected protein on productive performance in dairy cows - HALOI, SIKHAMONI; BHUYAN, ROBIN; SAIKIA, BIBEKA NANDA; BORAH, LAKHYAJYOTI; TALUKDAR, PAPORI; BARUAH, ANUBHA; BORA, JOGI RAJ; TAMULY, SHANTANU; HUSSAIN, JAKIR; SRIHITHA, SALUR; DIXIT, CHANDRA PRAKASH (The Indian Journal of Animal Sciences, 2025)
An experiment was conducted on lactating crossbred cows for assessing feeding effect of heat treated (HTSBM) and formaldehyde treated (FTSBM) soybean meal on productive performance of crossbred cows. Untreated soyabean meal (UTSBM) served as control group and HTSBM and FTSBM as treatment groups. Feeding of roughage and concentrate mixture having soybean meal (untreated) was offered in UTSBM group; while concentrate mixture with heat treated and formaldehyde treated soybean meal was offered to HTSBM and FTSBM group, respectively (n=8). Results showed that feeding HTSBM and FTSBM did not have significant effect on average dry matter (DM) intake (kg/Day) of cows. The cows fed HTSBM and FTSBM diets had a higher dry matter (P